2008
DOI: 10.3844/ajbbsp.2008.250.254
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Fuel Production from Algae as Renewable Energy

Abstract: Biodiesel is biodegradable, less CO 2 and NO x emissions. Continuous use of petroleum sourced fuels is now widely recognized as unsustainable because of depleting supplies and the contribution of these fuels to the accumulation of carbon dioxide in the environment. Renewable, carbon neutral, transport fuels are necessary for environmental and economic sustainability. Algae have emerged as one of the most promising sources for biodiesel production. It can be inferred that algae grown in CO 2 -enriched air can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(166 citation statements)
references
References 22 publications
3
146
1
8
Order By: Relevance
“…Therefore microalgae feedstock is better option because cultivating algae is easier than other food crops as it does not need any agricultural land and requires less doubling time (Chisti, 2007). It is a carbon neutral fuel, which does not add to total carbon emissions as it absorbs same amount of carbon dioxide during its growth phase (Hossain et al, 2008). Although the production of algae is much better than the other raw materials, but due to low lipid productivity, it is still not commercially viable (Nigam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore microalgae feedstock is better option because cultivating algae is easier than other food crops as it does not need any agricultural land and requires less doubling time (Chisti, 2007). It is a carbon neutral fuel, which does not add to total carbon emissions as it absorbs same amount of carbon dioxide during its growth phase (Hossain et al, 2008). Although the production of algae is much better than the other raw materials, but due to low lipid productivity, it is still not commercially viable (Nigam et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Li et al (2007) showed that it was feasible to grow microalgae, C. protothecoides, in a commercial scale bioreactor and also using 75% immobilized lipase, they claimed that 98.15% conversion could be obtained in 12 h when the reaction condition with respect to solvent type, water content, pH was optimized. On the other hand, Hossain et al (2008) studied biodiesel production from algal oils of macroalgae species Oedigonium and Spirogyra using sodium hydroxide as the catalyst and reported that it was possible to produce biodiesel using even low lipid containing macroalgae. Although there are few studies focused on biodiesel production from different algae species using homogeneous catalysts, such as NaOH and sulfuric acid, there are no studies on the biodiesel production from microalgae species using heterogeneous catalysts in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The species used in this study are microalgae. Cultivation of microalgae, a rapidly growing single-celled micro-organism, has also been suggested as a way to address the environmental issues of carbon dioxide (CO 2 ) greenhouse gas sequestration, generating renewable fuels, and wastewater remediation [2,3,4]. Alternative energy research is generally viewed as important considering the continuing and increasing per-capita global energy consumption, and the reported diminishing fossil fuel reserves [5,6].…”
Section: Introductionmentioning
confidence: 99%